Variasi Leksikal Berdasarkan Gender: Kajian Sosioleksikal pada Siswa SMP Bintang Persada Denpasar - Meutia Aulia Hakim; I Wayan Pastika; Ni Made Dhanawaty (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to describe the lexical variations that emerge based on gender factor within the sociolinguistic context of SMP Bintang Persada Denpasar. This research employs a descriptive qualitative approach using the observational method and note-taking technique by presenting a list of glosses to 20 eight-grade students, consisting of 10 male and 10 female participants. The lexical data were analyzed using the intralingual and extralingual comparison methods. The findings reveal significant lexical differences between the two speaker groups. Female student tend to use more varied, complete, and expressive lexical forms, including full words and phrasal expressions. In contrast, male students show a tendency to use shorter, more efficient lexical forms dominated by abbreviations and rough expressions. These findings highlight that gender functions as a linguistic marker shaping distinct communicative patterns among adolescents, with female students prioritizing social expression and affection, while male students emphasize practicality and efficiency in language use.